Kedaulatan Hukum Untuk Pendidikan: Membangun Fondasi Generasi Emas 2045 Dalam Perspektif Hukum Progresif - Hidayat, Wahyu; Kholik, Nur (Universitas Widya Gama Malang, 2025)
Legal sovereignty in education is an important pillar in building the foundations of Indonesia's golden generation in 2045. This legal sovereignty includes the application and enforcement of laws that are fair and equitable, as well as supporting the education system to create a conducive environment. The law plays a crucial role which is clearly stated in the law -1945 Constitution, Based on Article 31 of the 1945 Constitution, education is regulated as a right of every citizen which must be guaranteed by the state. The world of education in Indonesia has not yet received more attention from the government. Even though it is clear that the Law above mandates that the government should be able to carry out equality in all regions in order to achieve the vision of Golden Indonesia 2045 itself. The author concludes that legal sovereignty in education to build the foundations for the golden generation of 2045 in a progressive legal perspective is very relevant for the government to strive for, therefore the central government and regional governments as policy makers need to concentrate on implementing the Rule of Law in the World of Education in Indonesia.